2022
DOI: 10.3389/fneur.2022.931551
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of studies on the treatment of hemifacial spasm

Abstract: ObjectiveHemifacial spasm (HFS) is a common neurological disorder of the brain, which is difficult to treat. Most patients are distracted by it and are unable to work or study normally, which seriously affects their physical and mental health. However, there are a few bibliometric studies on it. This paper searched the articles on HFS using a bibliometric approach.MethodArticles about HFS were retrieved from the Web of Science (WoS) Core Collection database. We employed the Visualization of Similarities (VOS)v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A bibliometric analysis of hemifacial spasm (HFS) in 2022 reported that the second largest number (3.26%) of all HFS-related articles in the world were published from Sungkyunkwan university in South Korea where Prof. Kwan Park initiated the hemifacial clinic and personally performed over 5000 microvascular decompressions (MVD) for HFS [ 8 ]. We hereby present a concise overview with current updates of HFS.…”
Section: Discussionmentioning
confidence: 99%
“…A bibliometric analysis of hemifacial spasm (HFS) in 2022 reported that the second largest number (3.26%) of all HFS-related articles in the world were published from Sungkyunkwan university in South Korea where Prof. Kwan Park initiated the hemifacial clinic and personally performed over 5000 microvascular decompressions (MVD) for HFS [ 8 ]. We hereby present a concise overview with current updates of HFS.…”
Section: Discussionmentioning
confidence: 99%